Genomic structure of ST8-t008 USA300 and USA300-LV MRSA in the Rhine-Neckar Region, Germany, 2012-2018 - Klein, Sabrina; Boutin, Sébastien; Heeg, Klaus; Zanger, Philipp; Nurjadi, Dennis (International journal of antimicrobial agents, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) ST8-t008 of the pulsotype USA300 and the Latin American variant (USA300-LV) are the predominant virulent MRSA clonal lineages on the American continent. In Europe, the occurrence of USA300 or USA300-LV has often been related to international travel or outbreaks in hospitals. The replacement of local epidemic MRSA clones by these hypervirulent clones has not yet been demonstrated in Europe. This study aimed to gain insight into the genetic relatedness of ST8-t008 MRSA encountered in previous studies in the Rhine-Neckar Region, Germany, and ST8-t008 MRSA from other geographic regions.
Gesehen am 07.09.2022